Design of Microstrip Bandpass Filter with Defected Microstrip Structure (DMS) - Zakaria, Z; Mutalib, M. A; Mohamad Isa, Mohd Sa'ari; Zainuddin, N. A; Sam , W. Y; Othman , A.R (2013)
This paper presents a novel design of Chebyshev wideband bandpass filter (BPF) realized using microstrip with Defected Microstrip Structure (DMS) to produce bandpass and band reject characteristics simultaneously. This new class of filter is designed based upon λ_g0/4 short-circuited stubs structure of 7th degree. The filter exhibits wide bandwidth response from 3 to 6 GHz with a return loss, S11, better than - 20 dB and insertion loss, S21, of around -0.1 dB respectively. While, the DMS exhibit a band reject response better than -20 dB at a frequency of 5.2 GHz with a narrow bandwidth. Therefore, the integrated BPF and DMS produce wideband bandpass and band reject response simultaneously in order to remove any undesired signals in the passband of the bandpass response. This design is simulated on a Roger Duroid RO4350 with a dielectric constant,ε_r of 3.48 and a thickness of 0.508 mm. The simulation results show a promising performance that could be further examined during fabrication and experimental works in a laboratory. This type of filter is useful in any RF/ microwave communication systems particularly to eliminate any undesired signals in wideband applications. The reduction of overall physical volume and weight as well as cost and maintaining its excellent performance can also be achieved using this technique.